Neutralization of lymphocyte immortalization by different strains of Epstein-Barr virus with a murine monoclonal antibody. - Miller, G (1982)
A murine monoclonal antibody was raised against the B95-8 strain of Epstein-Barr virus (EBV), which was isolated from a case of mononucleosis after blood transfusion (Hoffman et al. Proc. Natl. Acad. Sci. U.S.A. 77:2979, 1980). We provide evidence that neutralization of immortalization by this monoclonal antibody is virus specific, since its potency was inversely related to the dose of challenge virus. Furthermore, the monoclonal antibody recognized antigens on viruses grown in human as well as in marmoset cells. We show that this monoclonal antibody neutralized three other transforming strains of EBV originating, respectively, from American patients with mononucleosis and fatal polyclonal lymphoma and from an African child with Burkitt lymphoma. However the antibody did not neutralize or detect antigens by immunofluorescence in the W91 strain of EBV. The hybridoma antibody did neutralize other EBV strains derived from the same Burkitt lymphoma cell line (Nyevu), as was the case with the W91 strain. This monoclonal antibody provides clear evidence of antigenic differences on the surface of EBVs and will ultimately prove useful in defining the antigenic site on EBV which elicits neutralizing antibody.